Penerapan Algoritma Linier Congruent Method Pada Aplikasi Pembelajaran Geografi - Syafira Zahara; Asriyanik Asriyanik; Winda Apriandari (Progresif: Jurnal Ilmiah Komputer, 2021)
Abstract The Covid-19 pandemic era caused the learning process to be carried out creatively, using media and other learning resources other than textbooks provided by the school, so that learning outcomes can be obtained optimally, especially for geography subjects. This article aims to create a geography learning media model in the form of a quiz that can be used as a learning support media, so that students can learn well, even in situations where they do not interact directly with the teacher. The media development method used is the Multimedia Development Life Cycle and the Linear Congruent Method to manage the randomization process. The components contained in the application are quizzes, word sequences, and puzzles. By using the LCM algorithm in regulating the randomization process, it is hoped that the questions that will be displayed are not easily guessed by students.Keywords: Linear Congruent Method, Multimedia Development Life Cycle, Geography learning application AbstrakEra pandemi Covid-19 menyebabkan proses pembelajaran mesti dilaksanakan secara kreatif, menggunakan media dan sumber-sumber belajar lain selain buku teks yang disediakan oleh pihak sekolah, agar capaian pembelajaran dapat diperoleh secara maksimal, khususnya untuk mata pelajaran geografi. Artikel ini bertujuan untuk membuat sebuah model media pembelajaran geografi dalam bentuk kuis yang dapat digunakan sebagai media pendukung pembelajaran, sehingga siswa dapat belajar dengan baik, walau dalam situasi tidak berinteraksi secara langsung dengan pengajar. Metode pengembangan media yang digunakan adalah Multimedia Development Life Cycle dan Linier Congruent Method untuk mengatur proses pengacakan soal. Komponen yang terdapat pada aplikasi berupa kuis, rangkai kata, dan puzzle. Dengan menggunakan algoritma LCM dalam mengatur proses pengacakannya, soal-soal yang akan ditampilkan diharapkan tidak mudah ditebak oleh siswa.Kata kunci: Linier Congruent Method, Multimedia Development Life Cycle, Aplikasi pembelajaran Geografi